Problemy wychowawcze w szkołach bazyliańskich w drugiej połowie XVIII wieku na przykładzie kolegium w Buczaczu - Lorens, Beata (Biuletyn Historii Wychowania, 2013)
Education problems in Basilian Schools in the latter half of the 18th century, with an example of the College in Buczacz. The literature concerning monastic education in the 18th century omits the subject of educational and teaching activity of Saint Basil the Great Monastery or discusses it very briefly. Not much is known about functioning of those schools in the period before the Commission of National Education was founded. The educational programme and the problems connected with it, which had occurred in Basilian schools were presented on the example of the college in Buczacz, located in the southeastern part of the Republic of Poland, functioning between 1754 and 1784. The educational goals pursued in the college were not different from the ones of other monastic schools. The then educational system mostly promoted the respect for ideological and moral values, considering material values less important. In the educational process, the Basilian Monks put piety first. The misdeeds of the students of the college in Buczacz were punished according to the canon of conduct of the then youth studying in monastic schools. The canon included: getting drunk, forbidden meetings with women, thefts, scuffles with soldiers in magnates’ service and stationed in the town, as well as with Jewish people. In the latter half of the 18th century, great significance was attached to proper conduct of the students of the college and misconducts against morals were the most common reasons for expulsions.